The Transcription Factor AtDOF4.7 Is Involved in Ethylene- and IDA-Mediated Organ Abscission in Arabidopsis - Wang, Gao-Qi; Wei, Peng-Cheng; Tan, Feng; Yu, Man; Zhang, Xiao-Yan; Chen, Qi-Jun; Wang, Xue-Chen (Frontiers in Plant Science, 2016)
Organ abscission is an important plant developmental process that occurs in response to environmental stress or pathogens. In Arabidopsis, ligand signals, such as ethylene or INFLORESCENCE DEFICIENT IN ABSCISSION (IDA), can regulate organ abscission. Previously, we reported that overexpression of AtDOF4.7, a transcription factor, directly suppresses the expression of the abscission-related gene ARABIDOPSIS DEHISCENCE ZONE POLYGALACTURONASE 2 (ADPG2), resulting in a deficiency of floral organ abscission. However, the relationship between AtDOF4.7 and abscission pathways still needs to be investigated. In this study, we showed that ethylene regulates the expression of AtDOF4.7, and the peptide ligand, IDA negatively regulates AtDOF4.7 at the transcriptional level. Genetic evidence indicates that AtDOF4.7 and IDA are involved in a common pathway, and a MAPK cascade can phosphorylate AtDOF4.7 in vitro. Further in vivo data suggest that AtDOF4.7 protein levels may be regulated by this phosphorylation. Collectively, our results indicate that ethylene regulates AtDOF4.7 that is involved in the IDA-mediated floral organ abscission pathway.